Changes to trade policy in Presidential Regulation 32/2022 on Neraca Komoditas - Krisna Gupta (Center for Indonesian Policy Studies (CIPS), 2022)
Legalized on February 21st 2022, Presidential Regulation No. 32/2022 on Neraca Komoditas is the implementing regulation of the Job Creation Law on trade. It regulates the use of and the procedure to enact Neraca Komoditas. The regulation provides a legal basis for the new Neraca Komoditas trade mechanism after the Government of Indonesia has promoted the idea in the past year (see Gupta, Pane, & Pasaribu, 2022 for early analysis on the Neraca Komoditas). The Neraca Komoditas will be rolled out for rice, salt, sugar, beef and fisheries products in 2022, while other goods that require export and import licensing will start to use Neraca Komoditas in 2023.
Keywords: 330